Plastic Change in the Auditory Minimum Threshold Induced by Intercollicular Effects in Mice - Hui-Xian Mei; Jia Tang; Zi-Ying Fu; Liang Cheng; Qi-Cai Chen (Neural Plasticity)
In the auditory pathway, the commissure of the inferior colliculus (IC) interconnects the two ICs on both sides of the dorsal midbrain. This interconnection could mediate an interaction between the two ICs during sound signal processing. The intercollicular effects evoked by focal electric stimulation for 30 min could inhibit or facilitate auditory responses and induce plastic changes in the response minimum threshold (MT) of IC neurons. Changes in MT are dependent on the best frequency (BF) and MT difference. The MT shift is larger in IC neurons with BF differences ≤2 kHz than in those with BF differences >2 kHz. Moreover, MTs that shift toward electrically stimulated IC neurons increase with the increasing MT difference between the two ICs. The shift in MT lasts for a certain period of time and then returns to previous levels within ~150 min. The collicular interactions are either reciprocal or unilateral under alternate stimulating and recording conditions in both ICs. Our results suggest that intercollicular effects may be involved in the acoustic experience-dependent plasticity of the MT of IC neurons.